Type of Participation of Rural Working and Non - Working women In Home Activities - Rathod, Shital; Solunke, Jyoti (IJRDO - Journal of Applied Management Science, 2017)
Homemaking is considered as one of the World’s major occupations involving acore of household activities essential for our existence, like any other professionhomemaking is also a profession. The present research study is planned with objectives tofind out the Personal characteristics of rural working and non working women, to knowthe type of participation of rural working and non working women, Assessment of Homeactivities of selected rural working and non working women will be investigated. Seventyfive (75) women from rural areas of Takli (Kumbhkarn) district Parbhani will be coveredfor the present study. This study will be investigated in one phases that was type ofparticipation of the rural working and non working women investigated.Results indicated that independent participation of the women was found inChapati/ bhakri making, serving food, Washing cloth, Mopping floor and Housedecoration. Joint participation with female was observed in Cleaning & cuttingvegetables and Actual preparation of curry while joint participation with male wasnoticed in ornaments purchasing and Cloth purchasing. Where as no participation ofrespondents were observed in Utensil purchasing, Medicine purchasing, getting themready for school, sending to tuition.